Perceptions and Potential of Integrating Elderly Schools and Complementary Therapy for Enhanced Basic Health Services - Rizky Erwanto; Dwi Endah Kurniasih; Muflih (Journal of Community Engagement in Health, 2024)
The aging global population necessitates tailored health services for the elderly. Complementary therapies, such as acupressure and exercise, have shown promise in addressing elderly health needs. Integrating these therapies with elderly schools, community centers offering tailored programs, presents a holistic healthcare approach. This research aims to assess elderly perceptions and potential benefits of integrating elderly schools and complementary therapies. It explores awareness levels, acceptance, implementation barriers, and perceived impacts on overall well-being. The study provides crucial evidence for policymakers and practitioners to enhance basic health services for the elderly. A descriptive survey method was employed, utilizing self-administered questionnaires. Closed-ended Likert scale questions gauged perceptions, while open-ended questions captured qualitative insights. The sample comprised individuals aged 60 and above, drawn from elderly school attendees and complementary therapy users. Survey results indicate positive perceptions toward integration, with approximately 85% of respondents expressing favorable views. Participants believe that combining educational programs with complementary therapies could enhance physical health (76%), mental health (68%), and stress management (82%). Open-ended responses provided nuanced insights, highlighting personal transformations and concerns related to cost and accessibility. The majority of respondents perceive the integration positively, supporting theoretical frameworks emphasizing benefits. Qualitative data enriches the understanding of participants' experiences. While acknowledging limitations, such as the cross-sectional nature and potential bias, this research provides valuable knowledge. It suggests that integrating elderly schools and complementary therapy holds promise in promoting holistic healthcare, contributing to healthy aging and improved quality of life for the elderly.